Praktik Kawin Paksa Dan Faktor Penyebabnya - Umar Faruq (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2019)
Marriage is an instinctive human demand, it is natural that two people of different genders, men and women, are mutually attracted to each other to live together and become husband and wife. When there is no spiritual and physical bond between husband and wife, this will cause problems in the couple's life so that the marriage does not last long and the path taken is divorce. This thesis research method uses a normative juridical research type (legal research), namely research that focuses on examining the rules or norms in positive law. The approach used by the author in writing this thesis is a statutory approach and a conceptual approach. The legal materials used in this thesis are primary legal materials, namely in the form of legislation, official records and judges' decisions, secondary legal materials, namely legal books written by legal experts, and non-legal materials in the form of books. -guidebooks for writing scientific papers and other non-legal materials obtained from the internet.